Tuning in RBC Growth Spectra - Benk, Szilard (IMF Working Papers; Working Paper ;, 2016)
For US postwar data, the paper explains central consumption, labor, investment and output correlations and volatilities along with output growth persistence by including a human capital investment sector and a variable physical capital utilization rate. Strong internal "amplication" results from an economy-wide productivity shock across goods and human capital investment sectors that has variances 10,000 fold smaller than in the standard RBC TFP shock. Simulated moments are compared to data moments for the business cycle, the low frequency and the Medium Cycle frequency, as well as the high frequency. A metric is provided to gauge that the results have an average of 46% deviation of simulated moments from data moments, for a broad array of targets across all windows. Within this array, key correlations have only a 15% deviation in the business cycle window, and growth persistence only an 8% deviation in the low frequency, which indicates good "propagation". Countercyclic human capital investment time and procyclic physical capital capacity utilization rates are also found as in data.